THE SHIFTING OF PRIVATE VEHICLE USERS TO PUBLIC TRANSPORT USERS (CASE STUDY : BALI, INDONESIA) - , I WAYAN ARNAYA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Bali has quite similar problems on traffic disorder compare to other city in Indonesia. One of the roots traffic congestion is high number of private vehicle which triggered by an increase in the number of population. Furthermore, the increasing of private vehicle tends to stimulate additional problems such as pollution, noise, and energy consumption. These circumstances cannot be neglected since it leads to the decreasing quality of life and threaten sustainability development. Numerous efforts have been conducted in order to solve those problems. Yet, the government remains focuses on build new infrastructure or based on conventional approaches. On the contrary, constructing the new infrastructure might even increase the demand of transport. Hence, in order to overcome traffic congestion through switching users of private vehicle to public transport, the affecting factor supposed to be examining first. Based on factor analysis, there are two major factor on transport mode choice in Bali